The rising global tide of non-communicable diseases: a call for decisive action - Ayomoh, FI (Houghton St Press, 2021)
The prevalence of non-communicable diseases (NCDs) has been on the rise and led to numerous deaths globally. Although the burden of disease of NCDs is significantly high, healthcare expenditure on the prevention and control of NCDs in most countries does not match the prevalence of NCDs. In low-and-middle income countries (LMICs), most development assistance for health has not been focused on NCDs with most donor funds addressing communicable diseases such as HIV/AIDS, Malaria and Tuberculosis. NCDs have plunged households into poverty as a result of catastrophic health expenditure from out-of-pocket payments for the management of NCDs. The recent COVID-19 pandemic has further highlighted the global prevalence of NCDs and the need for all countries to prioritize the prevention and control of NCDs. While some risk factors for NCDs are inherent and non-modifiable, exposure to other risk factors such as obesity, unhealthy diet, tobacco use and alcohol consumption can be curbed to reduce the incidence of NCDs. However, in most countries, especially in LMICs, the business interest of fast-food, tobacco and alcohol companies have hampered the implementation of prevention and control strategies for NCDs. Several cost-effective strategies for the prevention and control of NCDS have been outlined and have the potential to limit the global prevalence of NCDs to the barest minimum if adopted and implemented by most countries. It is imperative that global and national stakeholders take decisive action and renew their commitment to tackle the rising tide of NCDs across the globe.